2-Trifluoromethyl-1,3-diazabutadienes as Useful Intermediates for the Construction of 2-Trifluoromethylpyrimidine Derivatives - Medina-Mercado, Ignacio; Zaragoza-Galicia, Ivann; Olivo, Horacio F.; Romero-Ortega, Moisés (Synthesis, 2018)
A methodology to prepare 2-trifluoromethylpyrimidines has been developed on the basis of a cyclization reaction of 2-trifluoromethyl-1,3-diazabutadienes. These 2-trifluoromethyl-1,3-diazabutadienes were prepared by the condensation of trifluoroacetamidine and amide acetals or with chloromethaniminium salt derived from N,N-dimethylbenzamide with phosphorus oxychloride. The cycloaddition reactions of these 2-trifluoromethyl-1,3-diazabutadienes with DMAD and phenylacetyl chloride provided 2-trifluoromethylpyrimidine derivatives in regular to moderate overall yield.
Keywords: trifluoroacetamidine; cycloaddition reaction; 1,3-diazabutadienes; 2-trifluoromethylpyrimidines; trifluoromethyl group